Traditional use of medicinal plants in a city at steppic character (M'sila, Algeria) - Madani Sarri; Fatima Zahra Mouyet; Meriem Benziane; Amina Cheriet (GarVal Editorial Ltda., 2014)
Context: M'sila city occupies a privileged position in the central part of northern Algeria. The climate of this area is continental, subject in part to the Saharan influences of which vegetation is steppic. Aims: Highlight traditional usage of plants despite environmental characteristics. Methods: An ethnobotanical survey in the city of M'sila was conducted during the period 2011-2012 in collaboration with traditional practitioners, herbalists and healers. A total of 85 adults were able to determine the species and answer questions about the traditional use of plants in artisanal processing, nutritional and medicinal domains. Results: Medicinal plants recorded in the city of M'sila were 36 divided into 16 families and 31 genera. Lamiaceae family predominates (27.8%), followed by Asteraceae (13.9%). Leaves are the most frequently used (27.4%), the aerial parts (18.5%) and thus the seeds (16.3%). It appears that the population is highly dependent on these plants that allow them to treat different pathologies (digestive, stomach, diarrhea, constipation, vomiting) with a percentage (18.6%), carminative (5.7%) and antidiabetic (12.2%). In general, the remedies are administered orally. Indeed, therapeutic use forms are: the tisane or decoction (44.7%), infusion (27.1%) and powder (12.2%). Conclusions: The ethnobotanical survey conducted among traditional healers, herbalists and healers in the M'sila city has created an inventory of 36 species and a database that collected all the information on local and traditional therapeutic applications as well as all the diseases treated.